Brand Trust over Price Consciousness: Driving Generation Z Brand Loyalty in Online Travel Agencies - Lady Lady; Vanessa Stephanie; Wisnu Yuwono (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
While digital platforms frequently employ aggressive pricing to capture the Generation Z market, prior research yields inconsistent evidence on whether economic incentives or psychological factors more effectively secure long-term commitment. This study addresses this gap by examining the interplay between brand communication, online reviews, and brand loyalty, with brand trust as a mediator and price consciousness as a moderator. Using a quantitative approach, data were collected from 193 Gen Z consumers and analyzed through partial least squares structural equation modeling (PLS-SEM). The novelty of this research lies in identifying a